2012
DOI: 10.1111/j.1442-2018.2012.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived family functioning in depressed Chinese couples: A cross‐sectional study

Abstract: This study investigated family functioning in Chinese couples with a first episode of major depression, and in normal controls, and examined the association between depression severity and family impairment. Seventyfour patients with a first episode of major depression and 73 normal controls, together with their respective spouses, were assessed using the Family Assessment Device and Beck Depression Inventory. Patients with a first episode of major depression reported significantly higher Family Assessment Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…In this study, the average scores of problem-solving and emotional responses in the FAD were >3, which was significantly higher than that of normal controls (13). Problem-solving refers to the family's ability to solve problems that threaten family integrity and functional capacity.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, the average scores of problem-solving and emotional responses in the FAD were >3, which was significantly higher than that of normal controls (13). Problem-solving refers to the family's ability to solve problems that threaten family integrity and functional capacity.…”
Section: Discussionmentioning
confidence: 52%
“…Eliacik et al (2016) reported inverse associations between family functioning scores and depression and anxiety scores in Turkish mothers who have children with breath-holding spells. Wang and Zhao (2013) associated episodes of major depression with dysfunction in Chinese families. On the other hand, Tufiño Blass (2018) found significant associations between the problem-solving dimension of the Family Functioning Scale and the level of anxiety before school exams in Peruvian adolescents.…”
Section: Family Functioning and Symptoms Of Depression And Anxietymentioning
confidence: 99%
“…No entanto, durante esta fase de mudança, os relacionamentos com os amigos/parceiros expandem-se e ajudam os adolescentes a desenvolverem a sua autonomia (Wrzus et al, 2013). Uma vez mais, sendo que a comunicação familiar e as dificuldades familiares são dois aspetos fundamentais do funcionamento familiar, é natural que quanto maior sejam as dificuldades, a comunicação piore (Wang & Zhao, 2013). Deste modo, verificou--se através de um estudo que o funcionamento familiar apresentou uma associação negativa com o suporte social (Seibel et al, 2017).…”
Section: Quadrounclassified